A Contrapuntal Analysis of Othering in Rabindranath Tagore’s “Kabuliwala” and Tariq Rahman’s “Charity” - Ms. Yamima Edwin (University of Chitral Journal of Linguistics and Literature, 2022)
This research paper analyzes two modern short stories Rabindranath Tagore’s “Kabuliwala” and Tariq Rahman’s “Charity” through the conceptual lens of Othering. Within the broader theoretical framework of Postcolonialism, the concept of Othering entails the dichotomy of the Demonic Other and the Exotic Other. The mentioned writers, through their respective characters of the Kabuliwala and the Clerk, provide an insight into the stereotypical discourse which constitutes and permeates a society segregated on the basis of cultural and class differences. Through a contrapuntal analysis of the said texts, this paper explores how the dominant community perceives and stereotypes the marginalized as the Other. It also propounds the reasons behind the psychological constructions of fear and fascination revolving around the Other, which contribute to forming the image of the Demonic and Exotic Other. The aim of the paper is to make the readers realize the significance of the acceptance of the Other in order to build a society inclusive of all its multiple divisions.